2018
DOI: 10.1002/aoc.4458
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of silver nanoparticles using Thymus kotschyanus extract and evaluation of their antioxidant, antibacterial and cytotoxic effects

Abstract: Present study used ecofriendly, cost efficient and easy method for synthesis of silver nanoparticles (Ag NPs) at the room temperature by Thymus Kotschyanus extract as reducing and capping agent. Various analytical technique including UV–Vis absorption spectroscopy determined presence of Ag NPs in the solution, the functional groups of Thymus Kotschyanus extract in the reduction and capping process of Ag NPs are approved by FT‐IR, crystallinity with the fcc plane approved from the X‐ray diffraction (XRD) patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
88
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 208 publications
(102 citation statements)
references
References 33 publications
14
88
0
Order By: Relevance
“…The IC 50 of F. vulgaris , BHT and AgNPs@ Falcaria were 500, 404 and 318 μg ml −1 , respectively (Figure ). In agreement with our results, previous studies revealed that metal nanoparticles had strong antioxidant effects, and they removed various free radicals such as DPPH …”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The IC 50 of F. vulgaris , BHT and AgNPs@ Falcaria were 500, 404 and 318 μg ml −1 , respectively (Figure ). In agreement with our results, previous studies revealed that metal nanoparticles had strong antioxidant effects, and they removed various free radicals such as DPPH …”
Section: Resultssupporting
confidence: 93%
“…In agreement with our results, the study of Hamelian et al . revealed that when metal salts combine with biological compounds, their cytotoxicity is removed …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The contamination created by biosynthesis of nanoparticles by plant extracts is less than other methods and is approximately zero. Therefore, the biosynthesis of nanoparticles by plant extracts has fewer environmental and is more environmentally friendly . However, the production speed, quality, and other characteristics of the nanoparticles produced by plant extracts depend on factors such as nature of plant extract, concentration of extract, salt concentration, pH, temperature, and duration of the reaction .…”
Section: Introductionmentioning
confidence: 99%
“…As a rich source of ethno‐medicinal compounds, plants are commonly used for treatments of several diseases . The modern development of methods such as making herbal nanoparticles has attracted the attention of herb researchers and phytochemical researchers.…”
Section: Introductionmentioning
confidence: 99%